2019
DOI: 10.1038/s41419-019-1492-6
|View full text |Cite
|
Sign up to set email alerts
|

β-Thujaplicin induces autophagic cell death, apoptosis, and cell cycle arrest through ROS-mediated Akt and p38/ERK MAPK signaling in human hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC), a common liver malignancy worldwide, has high morbidity and mortality. β-Thujaplicin, a tropolone derivative, has been used in some health-care products and clinical adjuvant drugs, but its use for HCC is unknown. In this study, we found that β-Thujaplicin inhibits the growth of HCC cells, but not normal liver cells, with nanomolar potency. Mechanistically, we found that β-Thujaplicin could induce autophagy, as judged by western blot, confocal microscopy, and transmission electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
70
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 44 publications
10
70
0
5
Order By: Relevance
“…The MAPK signaling pathway is downstream of ROS and plays an essential role in the induction of apoptosis and autophagy 48 . Many studies have demonstrated that ROS accumulation could induce cell death through MAPK activation 49,50 . Western blot results indicated that apparent increases in the phosphorylation levels of ERK and JNK and NAC almost abolished this effect mediated by BD.…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK signaling pathway is downstream of ROS and plays an essential role in the induction of apoptosis and autophagy 48 . Many studies have demonstrated that ROS accumulation could induce cell death through MAPK activation 49,50 . Western blot results indicated that apparent increases in the phosphorylation levels of ERK and JNK and NAC almost abolished this effect mediated by BD.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 MAPK is an important transmitter of signals from the cell surface to the nucleus that can be activated by various extracellular stimuli such as cytokines, neurotransmitters, hormones, cell stress and cell adhesion. 39,40 NF-κB p65 and JAK2/STAT1 signalling pathways are involved in inflammation through complex molecular regulation. In a previous study, our team demonstrated that 15-Deoxy-△-12,14-Prostaglandin J2 (15d-PGJ2) can improve liver function by activating PPAR-γ to inhibit NF-κB p65, and the role and mechanism of the PPAR-γ natural ligand activator-15d-PGJ2 in liver has since reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…We next added PI in the amount of 5 μl in order to stain the cells followed by incubation for 5 min in the dark. Using BD FACS Calibur (BD Biosciences, Mountain View, CA, USA) we measured the levels and degree of cell apoptosis (Zhang et al, 2019a). For TUNEL analysis, briefly, cells were incubated with TUNEL labeling (marked with Green fluorescence) mix for 60 min at 37°C, and then we used DAPI (marked with Blue fluorescence, Sigma, USA) for double dyeing.…”
Section: Cell Cycle and Apoptosis Analysismentioning
confidence: 99%